A Limitless Urban Theory? A Response to Scott and Storper's 'The Nature of Cities: The Scope and Limits of Urban Theory'. (18th November 2015) - Mould, Oli
Abstract: The recent article in this journal by Scott and Storper (2015) suggested that the field of urban studies currently contains a multitude of varied theoretical viewpoints and argued for a unified general urban theory encompassing all urban scholarly work. Their proposal is that such a theory is based upon a foundational understanding of agglomeration and clustering. This response counter‐argues this, suggesting that such a proposal leaves urban theory too instrumental, deterministic and economistic. Moreover, Scott and Storper argue that there is a need to isolate the urbanization process from a wider suite of social, cultural and economic processes in which the urban is said to be 'embedded'. If we are to embrace a unified urban theory, however, it should be one which views cities as differing intensities of an urbanization process, and does not try to draw arbitrary boundaries about what is and what is not a city. If we are to strive for a general urban theory, then it would be far more beneficial to champion an ontology of an urbanization process with varying degrees of (de)intensification.